Studi Eksperimental Pengaruh Massa Pemberat Pada Sistem Penggerak Mekanisme Pembangkit Listrik Tenaga Oscillating Water Column - Arya, Rizky Nur; Arifin, Ahmad Anas; Ulum, Miftahul (Journal of System Engineering and Technological Innovation, 2024)
The demand for electrical power is increasing, and with the depletion of fossil fuel reserves, there are numerous opportunities to explore alternative energy sources. Ocean waves have emerged as a promising renewable energy option, particularly in developed nations. Given Indonesia's geography as an archipelagic country with numerous beaches, it is well positioned to harness the potential of ocean wave power plants. Among the various ocean wave power plant designs, the oscillating water column system stands out for its ease of implementation and minimal access requirements. This system operates by capturing the air pressure generated by ocean waves reaching the coast. A study was conducted to experiment with a prototype power generation mechanism that serves as both a pressure generator and a substitute for artificial waves in the oscillating water column power plant system. The objective of this study was to investigate the impact of varying ballast masses on pressure and power generation. The test results revealed that the minimum pressure and power output were recorded with a ballast mass of 0 kg, yielding a pressure of 214.62 N and a power output of 8.811 J/s. Conversely, the maximum compressive force and power output were achieved with a ballast mass of 2 kg, resulting in a compressive force of 235.2 N and a compressive power of 15.755 J/s. The highest efficiency was observed with a ballast mass of 2 kg, yielding an efficiency of 45%.